Timeliness of financial reporting in the shariah-compliantcompanies: effects of audit committee's and firms' characteristics / Syahrul Ahmar Ahmad, Siti Fabillah Mohd Yunos and Rahimah Mohamed Yunos - Ahmad, Syahrul Ahmar; Mohd Yunos, Siti Fabillah; Mohamed Yunos, Rahimah (UiTM Cawangan Johor, 2018)
The study examines the determinants of audit report delay among Shariah-compliant companies in Malaysia. Specifically, the study examines the relationship between audit report delay with selected audit committee's and firms' characteristics, namely audit committee independence, audit committee meeting, audit committee expertise, company size and its financial year end. This study also examined whether there is a difference in the period of audit delay after the revised Malaysian Code of Corporate Governance 2007 (MCCG 2007) took place. Multivariate analysis using 507 annual reports of these Shariah-compliant companies between 2006 till 2008 indicated that only audit committee meeting, audit committee expertise and company size showed significant relationships with audit report delay. The finding also showed that there is no significant difference between the period of pre and post implementation of the revised MCCG 2007. Findings of this study could provide new insight on the matters of audit report delay among Shariah-compliant companies in Malaysia.